Self-efficacy and adherence to structured lifestyle modifications in hypertension management: A cross-sectional study in Indonesian primary care - I.G.A. Mayoni Renanda Putri; Ni Kadek Ayu Suarningsih; Widyanthari Desak Made; Gusti Ayu Ary Antari (Nursing and Health Sciences Journal (NHSJ), 2026)
Hypertension remains a critical public health challenge in Indonesia, necessitating robust patient self-efficacy to sustain essential lifestyle modifications. The national CERDIK behavior program serves as a primary framework for facilitating such chronic disease self-management. This study aimed to evaluate baseline levels of self-efficacy and adoption of CERDIK behavior among hypertensive patients attending Primary Health Care II in West Denpasar. A descriptive-analytic, cross-sectional study was conducted involving 89 hypertensive patients selected via accidental sampling. Data collection utilized the validated Generalized Self-Efficacy Scale (GSES) alongside a modified CERDIK behavior questionnaire. Univariate analysis was subsequently performed to determine frequency distributions and central tendencies of the collected data. Findings revealed that a substantial proportion of respondents demonstrated high self-efficacy (46.1%) and high adherence to CERDIK behaviors (47.2%), reflecting a positive baseline for chronic disease management. A notable segment of the population exhibited moderate to low levels in both domains, indicating significant room for targeted clinical and behavioral intervention. Baseline self-efficacy and CERDIK behavior adoption are moderately favorable. Enhanced health education and consistent psychosocial support remain imperative to address these existing clinical gaps. Primary care providers must prioritize tailored educational interventions for newly diagnosed patients and individuals exhibiting low self-efficacy. Strengthening these community support systems is essential to optimize long-term hypertension management, improve overall treatment adherence, and prevent severe cardiovascular complications within the local population.